The Role of Uzbek Folk Instruments in the Educational Process - Olimov Sherali Botirovich (Researchparks Publishing, 2022)
This article is dedicated to the issue of Uzbek folk instruments, which gives them specific characteristics that affect the aesthetic education of students.